Features of autonomous regulation of cardiac activity in young athletes with juvenile ECG pattern - Mykhaliuk, Ye. L.; Horokhovskyi, Ye.; Bosenko, A.; Khoroshukha, M.; Михалюк, Євген Леонідович; Гороховський, Є.; Босенко, А.; Хорошуха, М. (My University, 2024)
The aim of the work is to study the occurrence of juvenile ECG pattern and characteristics of autonomous regulation of cardiac activity in young athletes with this ECG feature. Materials and methods. Electrocardiographic study and recording of heart rate variability (HRV) in children and adolescents of both genders engaged in various sports were carried out. Mathematical and spectral methods of HRV analysis were used to assess the state of mechanisms of neurohumoral regulation of the heart, activity of segmental and suprasegmental parts of the autonomous nervous system (ANS). Conclusions. Juvenile ECG pattern in the sample of examined young athletes was found almost equally in both boys and girls. In certain age groups, the largest number of young athletes with juvenile ECG pattern was registered. This ECG feature was combined with incomplete blockade of the right bundle branch of Gis and shortened QT interval syndrome. The analysis of HRV indicates a tendency to predominance of parasympathetic influences of ANS in boys, and a certain number of examined boys and girls had the indices of vegetative tone corresponding to normotonia. Мета роботи – вивчити виникнення ювенільної ЕКГ-ознаки та особливостей автономної регуляції серцевої діяльності у юних спортсменів із цією ознакою ЕКГ. Матеріали та методи. Проведено електрокардіографічне дослідження та реєстрацію варіабельності серцевого ритму (ВСР) у дітей та підлітків обох статей, які займаються різними видами спорту. Для оцінки стану механізмів нейрогуморальної регуляції серця, діяльності сегментарних і надсегментарних відділів вегетативної нервової системи (ВНС) використовували математичні та спектральні методи аналізу ВСР. Висновки. Юнацька картина ЕКГ у вибірці обстежених юних спортсменів виглядала майже однаково як у хлопців, так і у дівчат. В окремих вікових групах найбільша кількість юних спортсменів мала ювенільні ознаки ЕКГ. Такими ЕКГ-ознаками є неповна блокадою правої ніжки пучка Гіса та синдромом укороченого інтервалу QT. Аналіз ВСР свідчить про тенденцію до переваги парасимпатичних впливів ВНС у хлопчиків і лише у незначній кількості обстежених хлопчиків і дівчаток показники вегетативного тонусу відповідали нормотонії.
Особливості автономної регуляції серцевої діяльності юних спортсменів із ювенільною ЕКГ
Keywords: juvenile ECG pattern; young athletes; heart rate variability; age groups; юнацька ЕКГ; юні спортсмени; варіабельність серцевого ритму; вікові групи